THE EFFECT OF POLICY IMPLEMENTATION OF BASIC HEALTH SERVICES DURING THE COVID 19 PANDEMIC (Study of Implementation of Basic Health Services in West Java Province) - Sarihati, Tati; Santosa, Pandji (Universitas Padjadjaran, 2021)
Facing the Covid 19 pandemic, Indonesia is faced with the quality of essential health services that are still not optimal in various provinces. The main problems of vital health services that have emerged in West Java Province include the number and infrastructure of public health centers, the affordability of services and types of services such as maternal and child health, immunization, nutrition, environmental health and coverage of public health nursing performance. service quality variable, the theoretical approach of Fitzsimmons & Fitzimmons (2011) is used with Tangibles, Reliability, Responsiveness, Assurance and Empathy factors. The research method used is an informative survey approach by collecting data from library analysis sources and field experiments, including questionnaires, observations, and interviews. The sampling method used is Plain Random Sampling. The selected sample (n) was 92 people. The data analysis methodology used is route analysis. The results of the study reveal the positive and significant impact of policy implementation on the effectiveness of the quality of critical health services. In addition, it was also found that communication effectiveness variables that affect the quality of essential health services in West Java Province are also found